2013
DOI: 10.1159/000353663
|View full text |Cite
|
Sign up to set email alerts
|

The Surface Molecular Signature of Leukemic Cells Is Associated with <b><i>NPM1</i></b> Mutations and <b><i>FLT3</i></b>-ITD in Patients with de novo Acute Myeloid Leukemia

Abstract: Certain molecular mutations are associated with signs of cell morphology and differentiation in acute myeloid leukemia (AML). However, only limited data are available for the detailed analysis of such correlations. In this study, AML patients were classified into 4 subsets according to CD34, HLA-DR and CD11c expression levels. Significantly low CD34 antigen expression was observed in nucleophosmin (NPM1)-mutated patients and in those with FMS-like tyrosine kinase 3 internal tandem duplication (FLT3-ITD). No co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…This was further supported by our recent finding that FLT3/ITD mutations are present at the LSC level, which also showed that the oncogenic events of FLT3/ITD occurred at a cell stage possessing the IL-3 receptor α (CD123) [30]. This correlation forms a basis for CD123-targeted therapies in AML with intracellular FLT3 inhibitors [31]. …”
Section: Discussionsupporting
confidence: 56%
“…This was further supported by our recent finding that FLT3/ITD mutations are present at the LSC level, which also showed that the oncogenic events of FLT3/ITD occurred at a cell stage possessing the IL-3 receptor α (CD123) [30]. This correlation forms a basis for CD123-targeted therapies in AML with intracellular FLT3 inhibitors [31]. …”
Section: Discussionsupporting
confidence: 56%
“…A significant decrease in extracellular level of vascular endothelial growth factor (VEGF) has been associated with apoptosis following Res treatment in breast cancer cells (Garvin et al, 2006). Recent studies also suggest that Res inhibits SHH signaling in human chronic and acute myeloid leukemic (CML and AML) cells indicating that Res could be used as a potent agent for the treatment of some aggressive cancer types (Liao et al, 2012;Su et al, 2014). However, Res metabolites have very short half-life and are prone to rapid renal clearance.…”
Section: Introductionmentioning
confidence: 99%